Software-defined networking in cyber-physical systems: A survey. (February 2018) - Molina, Elias; Jacob, Eduardo
Abstract: Cyber-Physical Systems (CPSs) rely on networks that interconnect sensors and actuators to perform measurement, supervision and protection functions in different domains, such as transportation and industrial automation control systems. These networks must be able to support mobile wireless CPSs that are demanding new requirements related to flexibility and heterogeneity without compromising the Quality of Service (QoS). However, it is hard to determine, for example, the optimal resource allocation or the most reliable paths without global network information. In this way, the Software-Defined Networking paradigm is being considered as key to overcome such emerging needs. In particular, an SDN controller is able to establish paths between sensors and actuators according to bandwidth, latency, redundancy, and safety considerations. Thus, the goal of this paper is to review the state of the art of SDN approaches applied to mission-critical applications by identifying trends, challenges and opportunities for the potential development of software-defined cyber-physical networks.